Cover Picture: A Stable and Conductive Covalent Organic Framework with Isolated Active Sites for Highly Selective Electroreduction of Carbon Dioxide to Acetate (Angew. Chem. Int. Ed. 36/2022). Issue 36 (25th July 2022) - Qiu, Xiao‐Feng; Huang, Jia‐Run; Yu, Can; Zhao, Zhen‐Hua; Zhu, Hao‐Lin; Ke, Zhuofeng; Liao, Pei‐Qin; Chen, Xiao‐Ming
Abstract : Electroreduction of CO 2 to acetate provides a promising strategy to reduce CO2 emissions and store renewable energy, but acetate is usually a by‐product. A covalent organic framework with isolated active sites for the highly selective electroreduction of CO2 to acetate is reported by Pei‐Qin Liao and co‐workers in their Communication (e202206470 ). The copper–phthalocyanine active site with high electron density is conducive to the key step of C−C coupling of *CH3 with CO2 to produce acetate, and can avoid the coupling of *CO with *CO or *CHO to produce ethylene and ethanol.